Downstream Temperature Effects of Boreal Forest Clearcutting Vary With Riparian Buffer Width - M. Myrstener; C. Greiser; L. Kuglerová (Water Resources Research)
Abstract Clearcutting increases temperatures of forest streams, and, in temperate zones, the effects can extend far downstream of the clearcut itself. Here, we studied whether similar patterns are found in colder, boreal zones, and if riparian buffers can prevent stream water from heating up. We recorded temperature at 45 locations across nine streams with varying buffer widths. In these streams, we compared upstream (control) reaches with reaches at clearcuts and up to 150 m immediately downstream of the clearcut. In summer, we found daily maximum water temperature increases at clearcuts up to 4.1°C, with the warmest week ranging from 12.0°C to 18.6°C. We further found that warming was sustained 150 m downstream of clearcuts in three out of six streams with buffers <10 m. Surprisingly, temperature patterns in autumn resembled those in summer, yet, with lower absolute temperatures (maximum warming was 1.9°C in autumn). Clearcuts in boreal forests can indeed warm streams, and, because these temperature effects are propagated downstream, we risk catchment‐scale effects and cumulative warming when streams pass through several clearcuts. In this study, riparian buffers wider than 15 m protected against water temperature increases; hence, we call for a general increase of riparian buffer width along small streams in boreal forests.